Influence of the introduction of the ICD-10 on tendencies of mortality by causes (1980-2004) Influencia de la introducción de la CIE-10 en las tendencias de mortalidad por causas (1980-2004) - Diego Salmerón; Lluís Cirera; Marc Saez; Carmen Navarro (Elsevier, 2009)
Objective: To evaluate the influence of the tenth revision of the International Statistical Classification of Diseases (ICD-10) on tendencies of annual mortality rates, corrected and uncorrected to the ICD-9. Methods: Starting with the causes with a significant comparability ratio, we calculated the annual ageadjusted rates from 1980 to 2004. The comparability ratio was applied to the rates for 1999-2004, obtaining the corrected series for the whole period. This series was then compared with the uncorrected series using joinpoint regression. Results: Mortality decreased between 1999 and 2004. Differences were found in blood diseases, hypertensive diseases, cancer of illdefined sites, respiratory insufficiency, and myelodysplastic syndrome. Conclusions: The tendency of the main causes of mortality has been largely unaffected by the revisions in the ICD-10, except in infrequent or less specific diseases. Objetivo: Evaluar la influencia de la décima revisión de la Clasificación Estadística Internacional de Enfermedades (CIE-10) sobre las tendencias de las tasas anuales de mortalidad, con y sin corrección a la CIE-9. Métodos: Partiendo de las causas con razón de comparabilidad significativas, se calcularon las tasas anuales ajustadas por edad de 1980 a 2004. Se aplicaron a las tasas de 1999-2004 su razón de comparabilidad, y se obtuvo la serie corregida en todo el período, que se comparó con la serie sin corrección utilizando una regresión joinpoint. Resultados: La mortalidad disminuye en el período 1999-2004. Se encontraron diferencias en el grupo de enfermedades de la sangre, enfermedades hipertensivas, cáncer de sitios mal definidos, insuficiencia respiratoria y síndrome mielodisplásico. Conclusiones: La tendencia de las principales causas de mortalidad no se afecta por el cambio de revisión, excepto en enfermedades infrecuentes o poco específicas.